DIVORCE DUE TO ABANDONING PRAYER IN THE PERSPECTIVE OF THE SHAFI'I SCHOOL: AN ANALYSIS OF IMPLICATIONS FOR THE VALIDITY OF MARRIAGE - Syafiq Riza Hasan; Fathan Jihadul Islam; Farchan Mu’aziz; Ni'mazzad Al Bahiy; Lutfi Setiawan (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2026)
While prayer (salat) is a fundamental obligation in Islam, its abandonment triggers complex legal ramifications within the Shafi’i School, particularly concerning the continuity of marriage. However, a critical legal ambiguity persists regarding how specific motives for abandoning salat—whether through denial (juhud) or negligence (kasal)—distinctly impact the marital bond. This study addresses this gap by examining the research question: How does the Shafi’i School differentiate the legal status of marriage for individuals who abandon salat based on these distinct motivations? Employing a qualitative method with a literature review of classical Shafi’i jurisprudence (fiqh), the findings reveal that denial-based abandonment leads to apostasy (murtad), resulting in the immediate nullification (faskh) of the marriage. In contrast, negligence-based abandonment maintains the marital validity but subjects the individual to a mandatory three-day repentance period, the failure of which leads to legal termination. This study contributes to contemporary Islamic family law, particularly in the Indonesian context, by operationalizing classical jurisprudence to resolve modern marital disputes arising from religious non-compliance.